Toward Socio-Pragmatic Analysis of Persian Historical Drama: Based Bayhaqi’s History - Nabilu, Alireza; Taheri Asl, Mahdi (LANGUAGE ART, 2022)
This paper shows how classic Persian drama can be studied into pragmatics, utterances use three kinds of felicity conditions including content, sincerity and prepatory conditions. The violation of the mentioned conditions creates infelicitous model. It means that interlocutors disobey felicious conditions to convey their intentions successfully. The data samples taken from Beyhaqi history which is a historical drama resulting in tragedy which begins with the death of Ghaznavid great sultan, and ends with the destruction of a powerful chief minister. Adopting pragmatic analysis, present study investigates the dialogues of Bayhaqi’s History so that it intends to study how characters do their communicative purposes while they produce their utterances. The result of the research founded that because of caution, fear, and some cultural schema, the interlocutors use infelicitous strategies to make reader familiar with monarchy situation in which no one had right to freedom speech.